The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3329/bjvm.v14i1.28821
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Foot and Mouth Disease at Chuadanga Sadar Upazilla in Bangladesh

Abstract: A study on clinical observation, management and complication of foot and mouth disease (FMD) outbreak in cattle was carried out in Chuadanga sadar upazilla during 24 weeks period from July 2012 to January 2013. Clinical data were collected from 108 cattle of both sexes. The effect of season, breed, age, sex and purpose of keeping cattle on the incidence of the disease was analyzed. Seasonal variation of the disease was significant. Crossbred was found to be more susceptible than local breed. The prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The survey study on FMD outbreak during July 2017 to June 2018 in five divisions of Bangladesh shows higher incidence in native cattle (77.83%) than in crossbred cattle (55.43%) which mostly in accordance with Howlader et al (2004), Sorwar et al (2016) and Adhikari (2018) but higher than that reported by Giasuddin et al (2017) who found 56.5% and 77.8% positive case in indigenous cattle and crossbred cattle, respectively. This might be due to the fact that the study was confined in one specific area.…”
Section: Discussionsupporting
confidence: 78%
“…The survey study on FMD outbreak during July 2017 to June 2018 in five divisions of Bangladesh shows higher incidence in native cattle (77.83%) than in crossbred cattle (55.43%) which mostly in accordance with Howlader et al (2004), Sorwar et al (2016) and Adhikari (2018) but higher than that reported by Giasuddin et al (2017) who found 56.5% and 77.8% positive case in indigenous cattle and crossbred cattle, respectively. This might be due to the fact that the study was confined in one specific area.…”
Section: Discussionsupporting
confidence: 78%
“…However, in comparison to infected cattle, such complete medicine was found to have a considerable influence on the healing of FMD lesions. It is supported by Sorwar et al, (2016).…”
Section: Discussionmentioning
confidence: 97%